1974
DOI: 10.1177/002199837400800403
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Acoustic Emission During Fatigue Loading of Composite Specimens

Abstract: Strain and load controlled fatigue tests were run on boron-aluminum and boron-epoxy angle-plied specimens. Acoustic emission data was recorded using a gating technique that eliminated most extraneous noise. Various material parameters were monitored during the test. A good correlation between acoustic emission and damage extent and propagation was obtained. This was evidenced by an apparent first order linear relationship between dynamic compliance and totalized acoustic emission. A basis for an energy based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…Williams and Reifsnider (1974) showed that the AE rate generally correlated with the rate of stiffness reduction due to damage. Numerous attempts to identify sources of the AE signals in composites were made.…”
Section: Acoustic Emission Analysis Of Damage Mechanismsmentioning
confidence: 96%
See 1 more Smart Citation
“…Williams and Reifsnider (1974) showed that the AE rate generally correlated with the rate of stiffness reduction due to damage. Numerous attempts to identify sources of the AE signals in composites were made.…”
Section: Acoustic Emission Analysis Of Damage Mechanismsmentioning
confidence: 96%
“…Parametric AE analysis was used to evaluate overall damage accumulation in composites by Williams and Reifsnider (1974), Awerbuch and Ghaffari (1988), Bakuckas et al (1994), Ely and Hill (1995), Luo et al (1995), and Shiwa et al (1996). Williams and Reifsnider (1974) showed that the AE rate generally correlated with the rate of stiffness reduction due to damage.…”
Section: Acoustic Emission Analysis Of Damage Mechanismsmentioning
confidence: 99%
“…Acoustic emission was monitored during strain and load controlled fatigue tests of angle-plied boron/aluminum and boron/epoxy [16]. AE results were correlated with dynamic compliance and the study concluded that a good correlation could be established between the amount of AE and amount of damage, as well as between rate of emission and rate of damage development.…”
mentioning
confidence: 95%
“…Monitoring of AE during fatigue loading of composites has been investigated in [15][16][17][18][19][20]. Acoustic emission was monitored during strain and load controlled fatigue tests of angle-plied boron/aluminum and boron/epoxy [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation